A Review of the Literature of Surgical and Nonsurgical Treatments of Invasive Squamous Cells Carcinoma. (2nd April 2018) - Potenza, Concetta; Bernardini, Nicoletta; Balduzzi, Veronica; Losco, Luigi; Mambrin, Alessandra; Marchesiello, Anna; Tolino, Ersilia; Zuber, Sara; Skroza, Nevena; Proietti, Ilaria
Abstract : Cutaneous squamous cell carcinoma (cSCC) is an increasing public health problem. It is a primary malignant skin tumor with Malpighian differentiation and together with basal cell carcinoma is classified among nonmelanoma skin cancers (NMSCs). cSCC usually occurs on photoexposed areas, such as the head, the neck, and the extremities, and its incidence increases with age. Invasive forms of this skin tumor tend to be more aggressive showing a higher metastatic potential, usually regarding regional lymph nodes. Treatment options for invasive cSCCs include both surgical and nonsurgical options. The therapeutic choice depends on several factors, such as anatomic location, risk factors for tumor recurrence, age, and health status of the patient. This review aims to provide an overview of the current evidence on therapeutic surgical and nonsurgical management of invasive cSCC.